LONG-TERM ADMINISTRATION OF TAMSULOSIN INCREASE APOPTOSIS ON PROSTATE CELL OF BPH PATIENT: STUDY ON TGF-ß1, SMAD-4, AND NF- KB - Ghifary, Faathir Baihaqi; Daryanto, Besut; Mintaroem, Karyono (Indonesian Journal of Urology, 2025)
Objective: In this study we aimed to know further mechanism and relation between the long-term usage of tamsulosin with the apoptotic mechanism on prostatic cells of BPH patients qualitatively. Material & Methods: A Case-control study from prostate resection specimens. Subjects were 20 male who underwent the TUR-P procedure, were divided into two groups equally, a group who got long-term administration of tamsulosin 0.4 mg, and one without tamsulosin. TGF-β1 and Smad-4 expression was measured by Enzyme-Linked Immunosorbent Assay (ELISA), meanwhile expression of NF- kB measured by immunohistochemistry assay. Results: There was a significant difference on the Independent T-Test that showed an increase in expression of TGF-β1 and Smad-4 expression and a decrease in expression of NF- kB p= 0.003 (p<0,05) from a group of patients who got long-term oral administration of tamsulosin 0.4 mg, compared with a group of patients who didn’t get any treatment. Conclusion: Long-term tamsulosin would induce an apoptotic process in the prostate cells shown by the activity of TGF-β1, Smad-4, and NF- kB. Keywords: BPH, tamsulosin, TGF-β1, Smad-4, NF- kB, apoptosis